Proscription supports robust perceptual integration by suppression in human visual cortex - Reuben Rideaux (Nature Portfolio, 2018)
Perception relies on information integration but it is unclear how the brain decides which information to integrate and which to keep separate. Here, the authors develop and test a biologically inspired model of cue-integration, implicating a key role for GABAergic proscription in robust perception.